Konsep Persaudaraan Intra Agama Islam dalam Tafsir Nadhmuddurar Karya Al-Biqa’i - Ar-Rifa'i, Abdul Hannan (Ulumul Qur’an: Jurnal Kajian Ilmu Al-Qur’an dan Tafsir, 2022)
This study aims to explain and explain the concept of brotherhood in Islam according to al-Biqa'i in the Nadhmuddurar commentary book. This research was written using a literature study (Library Research) by reading and reviewing the literature that became the object of the research study. Based on this research, it can be concluded that al-Biqa'i in his book Nadhmuddurar explains the meaning of brotherhood and unity that cannot be separated because these two things are very urgent for the future of Muslims. Even in detail he explained that the degree or position of humans is not seen from lineage or descent but from piety.